Lack of Human Resources in the Mold Industry: Strategic Areas to Act On - Sousa, Daniela; Vitorino, Liliana (Journal of Tourism, Sustainability and Well-being, 2019)
In recent years, the mold industry has increased and nowadays it is considered an important export industry for Portugal. However, despite its new technology and modernization, the employers complain of a lack of human resources in this sector. Some CEO’s believe that many young students are not aware of the opportunities in this industry. This research analyses the main reasons for proximity and distance between students’ awareness and the reality of the industry and suggests some of the strategic areas on which we can act on in order to solve the problem. These areas are the unawareness of reality and the industry opportunities; the insufficiency of a practical component in teaching; the expected salary of the students leaving the higher education maladjusted to reality; the long and uncertain working hours; and the unawareness of the job profiles and career plans in the industry This research also tries to achieve some guidelines which can be used for future procedures in mold enterprises, schools or eventually other industries with the same problem.